Analysis of Proton Persona side door (driver) using simulation tool - Raja Ashrafuzzaim, Raja Zolkiply (2008)
Automobile safety is the avoidance of automobile accidents or the minimization of harmful effects of accidents, in particular as pertaining to human life and health. Numerous safety features have been built into cars for years. Safety is divided into two categories, active and passive. Active Safety is systems that use an understanding of the state of the vehicle to both avoid and minimize the effects of a crash. These include braking systems, like brake assist, traction control systems and electronic stability control systems to help the driver control the vehicle. Meanwhile, passive safety refers to built-in features of a vehicle that help reduce the effects of an accident, such as crumple zones, seatbelts, strong body structures and airbags . Impact test is conduct in 5 different ways such as side, front, pole rollover and offset. During side collision, physical event is a complicated transfer of momentum from striking car to struck car. This project consists of two steps. First is. to develop solid model by using 3D scanner and convert into simulation environment. Second is to do simulation which consists of setting the boundary condition for restraint, force and then meshing the model. The final result leads to finding that Proton Persona needs stiffer structure as unit body or by increase the numbers of impact bars. From simulation the numbers of impact bars differentiate the stress, strain and displacement result and the value clearly shown in chapter four. All result decreasing as numbers of bars added. The impact bars, outer panel and inner panel, is not enough to absorb the force applied .More on bars will reduce the stress, strain and displacement of the door.